Ramón Otero Pedrayo in Latin America: Homo Viator - Arias Chachero, Patricia (Madrygal. Revista de Estudios Gallegos, 2023)
Ramón Otero Pedrayo, a key figure in prewar and postwar Galician literature, traveled to Latin America three times (1947, 1956, and 1959). These trips meant the possibility of meeting old friends, such as Castelao, and the reestablishment of communication, in the midst of the dictatorship, between the Galician supporters who stayed in Galicia and those who went into exile.
Keywords: Ramón Otero Pedrayo; Latin America; Travel; Exile; Dictatorship